Tratamento térmico da lama do beneficiamento de rochas ornamentais: aplicação como pozolana em matrizes cimentícias - Uliana, Juliana Gavini (2014)
There are many researches grounded in the possibility of the use of industrial byproducts as an alternative building materials which promotes the sustainable development of civil construction and other sectors of the industry. Brazil has a highlighted position worldwide regarding the ornamental rock production, such that this sector contributes in a positive manner to the development of the country. However, the processes involved in the ornamental rock fabrication generate a significant volume of waste, especially in the stage of processing, with the transformation of rock blocks in plates. The sawing of the rock blocks can be done using traditional looms (using metal blades watered by an abrasive pulp composed of water, lime, rock dust and steel grit) or using multiwire looms (where diamond coated wires cut the blocks with water spray). The waste sludge generated in those two different process is separated into two categories, residue with steel shot and residue without steel shot, being to the latter one added the polishing residue which are destined to landfills, requiring recycling methods due their environmental impact. This research aims to verify the application of heat treating procedure on the slurry residue from the processing of ornamental rocks in their condition with steel grit (LBRO G) and without steel grit (LBRO D), to produce pozzolanic material, as an alternative to the reinsertion of this waste in the supply chain. To this end, the wastes are characterized and subjected to tests to identify the necessary methods to obtaining glassy material, created by heat treatment and grinding. These produced materials were characterized and their mechanical behavior were evaluated in mortars with cement replacement in amounts of 5, 10, 15 and 20% by volume for verification of pozzolanic activity, comparing the results with mortars produced with waste without heat treatment. It can be concluded that the results of compressive strength for the studied mortars were promising, which was possible to verify that after heat treatment, the residue treated presented pozzolanic characteristics.